(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women writers in India are moving forward with their strong and sure strides, matching the pace of the world, we see them bursting out in full bloom spreading their own individual fragrances. They are recognized for their individuality, originality and the indigenous flavor of the soil that they bring to their work. Yes, they are our women writers, writers first, I must insist. Gender is only incidental……but, one must admit, it does spice up their work. We see Indian women writers like Shahs Despande, Arundhati Roy, Anita Desai, Kamala Das and Shaba De, just to name a few who hold their own in the woman writer’s world of initial rejection, dejection, familial bonds, domesticity and what not. It is amazing to note that these writers and many more have climbed the ladder of success the slow and painful way. Kamala Das is beyond doubt the greatest woman poet in contemporary Indo-Anglican Literature. A confessional poet, she displays feminist ethos in her poems. She wrote chiefly of love, its betrayal, and the consequent anguish, and India readers responded sympathetically to her guileless, guiltless frankness with regard to sexual matters. Kamala has surely out grown Victorian models and accepted sex and sensuality as an integral part of poetry. Many of her poems are suffered with warmth and passion, with heat of an unrequited love and unfulfilled desire. According to Dr. V. Alexander Raja, “In the poems of Kamala das, we find a rare body and its feelings and she seems incapable of thinking of eternal life as a bodiless existence. This peculiar stance may be the reason why she is drawn to Islamic religion with its different concept of life afterlife.” Frustrated by love and loneliness, she longed for an eternal life with her body and soul after her life on the earth. She loved her body as much as she loved her soul. Since her bodily desires could not be satisfied by her life here she wants to achieve it by a life after death. Kamala’s confessional poetry is obsessively mulling over love and ‘the body’s wisdom’, like Whitman that is why Iyengarcalls her ‘Femme Fatal’ whose poetry is of pelvic region. In her poetry, love appears in several roles such as ‘skin communicated thing’, as overpowering force, an escape, a longing and a hunger resulting in society.